A Metalless and Fungicide-Free Material Against Candida: Glass-Loaded Hydrogels - Gabrielle Caroline Peiter; Elane da Silva Salvador; Fabián Ccahuana Ayma; Kádima Nayara Teixeira; Silvia Jaerger; Rafael A. Bini; Cleverson Busso; Rodrigo José de Oliveira; Ricardo Schneider (Pharmaceutics, 2025)
Background/Objectives: We report the antifungal potential of transition metal-free borophosphate glass-loaded hydrogels (BGHs) with different phosphorus/boron molar ratios (P/B = 2, 1, and 0.5) against Candida species. Candida yeasts pose a significant health risk as they can cause infections, systemic diseases, and even potentially fatal complications in immunocompromised individuals. Methods: The antifungal activity of BGH was evaluated against Candida albicans, Candida tropicalis, Candida krusei, and Candida glabrata using kinetic growth analysis, the agar well diffusion method, the minimum inhibitory concentration, the minimum fungicidal concentration, and scanning electron microscopy. Results: All BGH formulations effectively inhibited yeast growth at various concentrations, with results comparable to commercial miconazole gel (CMG). Hydrogels with P/B ratios of 0.5 and 1 produced larger inhibition zones than CMG, except against C. glabrata. However, BGHs with a P/B ratio of 0.5 at 3% and 5% (w/w) demonstrated relevant antifungal activity, especially against C. albicans and C. tropicalis. Conclusions: These findings highlight the promising antifungal potential of borophosphate glass-based hydrogels, particularly those with high boron content. Their efficacy against multiple Candida species suggests they could serve as an alternative to conventional antifungal agents.